(untitled) (International Journal of Medical and Surgical Sciences, 2021)
Introduction: The modern management of cancer treatment requires access to the venous system repeatedly for the passage of drugs, fluids and blood components. Peripheral veins are rapidly damaged by repeated punctures and by fluids that pass through them. To solve this problem, long-term vascular accesses avoid repeated punctures. One type of long-term venous access is the Port-A-Cath, which is an implantable device usually in the chest with a central venous catheter. Case report: Next, the case of a 34-year-old female with a diagnosis of breast cancer in the right breast is presented. It is treated with a radical mastectomy, and after the procedure a port-a-cath is placed in the left subclavian route for future treatments. The first cycle of chemotherapy is performed, later the patient reports pain at the catheter placement site with increased volume and progressive increase in pain. The patient goes to her health center for an evaluation, they decide to take a chest X-ray showing the migration of the catheter. The management used was through the seldinger technique at the femoral puncture site with a 6 Fr Amplatz GooseNeck Snare Guide, with which it was possible to extract the foreign body at the level of the left brachiocephalic vein. Conclusion: The implantation of a Port-A-Cath catheter is associated with some risks in the process. Catheter and patient care should be maintained to decrease the incidence of complications.